2014
DOI: 10.1097/prs.0000000000000006
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine Green SPY Elite–Assisted Sentinel Lymph Node Biopsy in Cutaneous Melanoma

Abstract: Diagnostic, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 23 publications
1
52
0
11
Order By: Relevance
“…This is supported by previous studies that have shown consistently delayed visualization of blue dye when used in combination with ICG . Despite the low success rate of ISB in this study, our findings are similar to others which have reported inferior results of blue dyes compared to ICG .…”
Section: Discussionsupporting
confidence: 92%
“…This is supported by previous studies that have shown consistently delayed visualization of blue dye when used in combination with ICG . Despite the low success rate of ISB in this study, our findings are similar to others which have reported inferior results of blue dyes compared to ICG .…”
Section: Discussionsupporting
confidence: 92%
“…Die ermittelte Fehldetektionsrate durch ICG von 10 % lag in der Varianz von 0-20 % (Tabelle 2 ), die in der Literatur angegebenen wurde. Ein Vorteil ergibt sich vor allem bei bekanntermaßen variierenden lymphatischen Abfl ussmustern am Stamm oder auch limitierenden anatomisch engen Verhältnissen im Kopf-Hals-Bereich [ 35,36 ] , wobei die mit dem Fluoreszenz-Verfahren erreichte Detektionssicherheit angesichts relativ inhomogener Ergebnisse in diesen anspruchsvollen Lokalisationen weiterhin kontrovers zu diskutieren ist [ 18,34,37 ] . Bei angegebenen Raten von 0-63 % (Tabelle 2 ) unterscheiden jedoch nur wenige Publikationen zwischen einer transdermalen, einer in-situ-oder ex-situ-fl uoreszenzoptischen Identifi zierung des SLN durch das ICG-Verfahren [ 33,34 ] .…”
Section: Diskussionunclassified
“…Ein Vorteil ergibt sich vor allem bei bekanntermaßen variierenden lymphatischen Abfl ussmustern am Stamm oder auch limitierenden anatomisch engen Verhältnissen im Kopf-Hals-Bereich [ 35,36 ] , wobei die mit dem Fluoreszenz-Verfahren erreichte Detektionssicherheit angesichts relativ inhomogener Ergebnisse in diesen anspruchsvollen Lokalisationen weiterhin kontrovers zu diskutieren ist [ 18,34,37 ] . In 20 % aller Patienten -wie auch in der hier vorgestellten Studie-ist daher ein völliges Fehlen jeglicher Färbung zu verzeichnen [ 18,[40][41][42] . Die Dosierung des ICG variiert mit verabreichten Mengen von 2 μ g bis 5000 μ g in den bisherigen Studien jedoch erheblich (Tabelle 2 ).…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…Since 2011, at least seven series of NIR fluorescence imaging of skin cancer have emerged. [58][59][60][61][62][63][64][65] However, no conclusive or long-term evidence that NIR fluorescence imaging is superior to current techniques exists. Because NIR fluorescence imaging is highly sensitive it may be superior for detecting small nodes overlooked by RI and dye.…”
Section: Skin Cancermentioning
confidence: 97%